2019
DOI: 10.1111/mmi.14218
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial NHEJ: a never ending story

Abstract: Double-strand breaks (DSBs) are the most detrimental DNA damage encountered by bacterial cells. DBSs can be repaired by homologous recombination thanks to the availability of an intact DNA template or by Non-Homologous End Joining (NHEJ) when no intact template is available. Bacterial NHEJ is performed by sets of proteins of growing complexity from Bacillus subtilis and Mycobacterium tuberculosis to Streptomyces and Sinorhizobium meliloti . Here, we discuss the contribution of these models to the understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 105 publications
0
52
0
Order By: Relevance
“…Briefly, upon the formation of DSBs, dimeric complexes of Ku proteins bind to DSBs, and then recruit LigD to process the DNA termini, either resecting or synthesizing, or even reconstructing the original complementary ends. Finally, the break is sealed by LigD (Figure ) …”
Section: Repair Of Dna Double‐strand Breakmentioning
confidence: 99%
See 4 more Smart Citations
“…Briefly, upon the formation of DSBs, dimeric complexes of Ku proteins bind to DSBs, and then recruit LigD to process the DNA termini, either resecting or synthesizing, or even reconstructing the original complementary ends. Finally, the break is sealed by LigD (Figure ) …”
Section: Repair Of Dna Double‐strand Breakmentioning
confidence: 99%
“…Utilizing NHEJ process to repair the DSB delivered by Cas nuclease provides a striking feature that the homologous repair template is no longer required, which may significantly simplify the CRISPR‐based genome editing strategy in prokaryotes, enabling the construction of the single‐gene knockout library with substantially reduced labor. However, NHEJ mechanism is present in limited bacterial species, such as M. tuberculosis , M. smegmatis , B. subtilis , and Streptomyces species . A recent study in M. smegmatis demonstrated that the intrinsic NHEJ machines, Ku and LigD, worked efficiently to repair the DSB delivered by FnCpf1 in an error‐prone manner, giving an editing efficiency up to 70% for certain genes .…”
Section: Repair Of Dna Double‐strand Breakmentioning
confidence: 99%
See 3 more Smart Citations